Self-regulation and the specificity of autobiographical memory in offenders - Neves, Daniela (2019)
Certain clinical populations exhibit an Overgeneral Autobiographical Memory (OAM), characterized by difficulty remembering specific events. One study has observed OAM for positive events in a group of offenders. This study analyzed the stability of the valence effect in the OAM of offenders, the executive control impairments facilitating OAM in offenders, and the relationship of self-esteem and social desirability with AM specificity. The specificity (Autobiographical Memory Test) and emotional properties of the AMs of 59 prisoners (30 men, 29 women) and a control group (29 men, 30 women) were compared. Social desirability, depression symptoms, self-esteem and executive functions (Mazes, Stroop, Verbal Fluency) were assessed. The offenders recalled fewer specific positive AMs than controls, and did not perceive the emotional intensity of their negative AMs to decrease over time, unlike the controls. The offenders' recall of specific negative AMs seemed to influence negatively their performance in the subsequent executive control tasks. Dysfunctional coping strategies in offenders were related to OAM, but not social desirability or self-esteem.